The rule that a spouse cannot forfeit at divorce what he or she has contributed to the marriage: an argument for chance - Bonthuys, Elsje (Juta Law, 2014)
Unlike other systems of family law, South African law allows parties to choose their matrimonial property system by way of antenuptial contract. Although the financial consequences of the dissolution of marriage follow broadly from the chosen matrimonial property system, certain statutory and common-law mechanisms allow for a variation from the rigours of the applicable property regime. This article concerns one of these mechanisms, namely forfeiture of benefits in terms of s 9 of the Divorce Act 70 of 1979.
Keywords: Forfeiture orders; Divorce; Marriage; Forfeiture of benefits; Gender discrimination; Forfeiture of divorce